The Effect of Role-Play on the Development of Dialogue Skills among Learners of Arabic as a Second Language - Ayman Sabry Daif-Allah; Muhammad Sultan Al-Sultan (MDPI AG, 2023)
Dialogue is one of the most important methods of achieving a desired goal and persuading others to accept a certain idea. This research aims to identify the effect of the role-play strategy on the development of dialogue skills among advanced-level students in the Arabic Language Teaching Unit for Non-Native Speakers at Qassim University. Using the quasi-experimental approach, the study was administered to 50 students, 25 students in the experimental group and the same number in the control group. The experimental group was taught through role-play, while the control group was taught through the traditional textbook-based methods. Quantitative data were collected by means of a dialogue skills assessment scale designed to assess the designated dialogue skills of the study sample. A quantitative analysis of the results showed a positive effect of role-play on the development of dialogue skills in terms of self-esteem, good listening, the expression of opinion, and respect for others. The results also showed that the simulation of real-life situations motivated students to develop dialogue skills in an organized manner. The results also highlighted the positive and negative aspects of using role-play in enhancing dialogue skills of learners of Arabic as a second language. The study recommends expanding the use of the role-play strategy in teaching the various basic skills of the Arabic language to the non-native speakers at Qassim University. It also suggests useful ideas for other researchers to study innovative techniques for improving the acquisition of language skills among learners of Arabic as a second language.